2007
DOI: 10.1590/s1679-87592007000200001
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessment of sediments from the Port of Santos and the disposal sites of dredged material

Abstract: A B S T R A C TThe dredging of sediments from the Santos Channel is necessary to allow the navigation of ships operating in the Port of Santos. The disposal sites for such sediments are situated on the coastal zone, in front of the Santos Bay. The present paper aimed at evaluating the toxicity of sediments collected at the Santos Channel and at the former and current sediment disposal sites. Whole sediment tests with amphipods and elutriate assays with sea-urchin embryos were used. The samples from the Santos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 9 publications
1
17
0
12
Order By: Relevance
“…In this context, the local ecosystems and biota are under risk, in particular those related to the unconsolidated substratum, since the sediments are toxic and contaminated by metals, poly-aromatic hydrocarbons (PAHs), poly-chlorinated biphenyls (PCBs), detergents and other substances (CESAR et al, 2007;SOUSA et al, 2007;LAMPARELLI et al, 2001;MEDEIROS;BÍCEGO, 2004;HORTELLANI et al, 2005;ABESSA et al, 2008). However, despite such authors have showed that the contamination of SES sediments can affect the water column organisms, the actual effects still are unknown and need to be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the local ecosystems and biota are under risk, in particular those related to the unconsolidated substratum, since the sediments are toxic and contaminated by metals, poly-aromatic hydrocarbons (PAHs), poly-chlorinated biphenyls (PCBs), detergents and other substances (CESAR et al, 2007;SOUSA et al, 2007;LAMPARELLI et al, 2001;MEDEIROS;BÍCEGO, 2004;HORTELLANI et al, 2005;ABESSA et al, 2008). However, despite such authors have showed that the contamination of SES sediments can affect the water column organisms, the actual effects still are unknown and need to be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to their geographical characteristics, estuaries have been severely impacted, not only by direct destruction, to make room for anthropic structures such as cities, industrial facilities, aquaculture farms, ports and harbors, marinas and others, but also because they are threatened by pollution, resulting in a variety of biological effects, from biochemical and genetic disturbance to ecological imbalance, which could threaten the ecological processes and consequently the economic exploitation of biological resources, with negative effects on the economy. Aquatic pollution may also affect human health by leading to the consumption of contaminated seafood (CLARK 1997; VAN DER OOST et al, 2003;SOUSA et al, 2007;ABESSA et al, 2008, PEREIRA, et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the sediment is the great reservoir of the pollutants that may be made available by means of physical effects, such as bioturbation, diffusion or dredging (BELZUNCE et al, 2001 andCHAPMAN et al, 1987), in the case of the Santos Channel and dredged material disposal area (SOUSA, 2007 andARGENTINO-SANTOS 2006).…”
Section: Methodsmentioning
confidence: 99%
“…SOUSA et al (2007) evaluated sediment quality in the Santos Channel using acute ecotoxicological assays with T. viscana in six samples of whole sediment obtained from the Piaçaguera Channel as far as Ponta da Praia, and seven samples from the dredged material disposal area by means of chronic effect test with sea urchin embryos and elutriate, as well as the presence of contaminants in this area.…”
Section: Methodsmentioning
confidence: 99%